Growth and Body Size of the Harbour Porpoise, Phocoena phocoena (Cetacea, Phocoenidae), in the Sea of Azov and the Black Sea - Gol'din, P. E. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
Изучены постэмбриональный рост, некоторые особенности биологии и размеры тела морской свиньи. Средняя длина тела новорожденных — 72,5 см; период рождений растянут не менее чем с апреля по август. Максимальная продолжительность жизни — не менее 20 лет, возраст достижения половой зрелости — 3–4 года, физической зрелости — 6–12 лет. Длина тела взрослых самцов и самок в Азовском море в среднем составляет соответственно 132–135 и 143–145 см, в Черном море — 122–124 и 132–134 см. Вопрос о правомерности выделения отдельных периодов роста в постнатальном онтогенезе остается открытым. Целесообразно выделять два периода замедляющегося роста. Впервые обнаружены факты, подтверждающие существование обособленных популяций в Азовском и Черном морях: взрослые азовские особи крупнее черноморских на 10–12 см. В течение последнего столетия произошло некоторое уменьшение размеров особей. Морские свиньи изученного региона явля¬ются в наши дни самыми мелкими представителями вида P. phocoena. Postnatal growth, some aspects of life history, and body size of harbour porpoise were studied. The mean body length of neonates is 72.5 cm; the calving sea¬son lasts at least from April to August. The maximum life span is at least 20 years; the age at attain¬ment of sexual maturity is 3–4 years, of physical maturity — 6–12 years. The mean body length of adult males and females is 132–135 cm and 143–145 cm respectively in the Sea of Azov, 122–124 cm and 132– 134 cm in the Black Sea. The question still remains of the existence of two growth stages in postnatal ontogenesis of harbour porpoises. It seems reasonable to distinguish two stages, each with decreasing growth rate. The first evidences are found for the existence of separate populations in the Sea of Azov and the Black Sea: adult specimens from the Sea of Azov are larger than those from the Black Sea in 10–12 cm. During the 20th century body size of the animals has somewhat reduced. The harbour porpoises in the studied region are at present the smallest representatives of P. phocoena species.